Ethnic conflicts in hillside borderlands: a study on headhunting in eighteenth- and nineteenth-century Taiwan - Hung, Li-Wan (Modern Asian Studies)
This article examines ethnic conflicts in hillside borderlands, with special emphasis on the tradition of headhunting. Moreover, this study investigates how the self-autonomous new settlers negotiated with the aboriginal tribes to establish their living space, as well as the social relationships that were formed as a result. The findings of this study reveal, on the one hand, the multiple meanings of the headhunting custom and its evolution following the influx of new settlers and under Qing statecraft, and, on the other hand, shed light on how immigrants established their living space in the face of complex ethnic relationships and conflicts in the hillside borderlands. Although the practice of headhunting did not have its roots in conflicts between mountain inhabitants (shengfan) and plains immigrants (shufan and Han Chinese), changes in the nature and scale of headhunting in the eighteenth and nineteenth centuries were the result of the mass influx of new settlers and state intervention. In borderland regions where government authority was not well established, immigrants were left to fend for themselves and were much affected by the local cultural environment. Hence, when analysing the development of immigrant society or local history, due attention should be paid to the social traditions and characteristics of native inhabitants, which often provided the background and underlying reasons for ethnic conflicts. - Reproduced
Keywords: Ethnic conflicts, Violence